Inhibition of the Arabidopsis Salt Overly Sensitive Pathway by 14-3-3 Proteins . Issue 3 (21st March 2014) - Zhou, Huapeng; Lin, Huixin; Chen, She; Becker, Katia; Yang, Yongqing; Zhao, Jinfeng; Kudla, Jörg; Schumaker, Karen S.; Guo, Yan
Abstract : This study demonstrates that 14-3-3 proteins negatively regulate a pathway conferring salt tolerance in plants by repressing the activity of a participating kinase in the absence of salt stress. Abstract: The Salt Overly Sensitive (SOS) pathway regulates intracellular sodium ion (Na + ) homeostasis and salt tolerance in plants. Until recently, little was known about the mechanisms that inhibit the SOS pathway when plants are grown in the absence of salt stress. In this study, we report that the Arabidopsis thaliana 14-3-3 proteins λ and κ interact with SOS2 and repress its kinase activity. Growth in the presence of salt decreases the interaction between SOS2 and the 14-3-3 proteins, leading to kinase activation in planta. 14-3-3 λ interacts with the SOS2 junction domain, which is important for its kinase activity. A phosphorylation site (Ser-294) is identified within this domain by mass spectrometry. Mutation of Ser-294 to Ala or Asp does not affect SOS2 kinase activity in the absence of the 14-3-3 proteins. However, in the presence of 14-3-3 proteins, the inhibition of SOS2 activity is decreased by the Ser-to-Ala mutation and enhanced by the Ser-to-Asp exchange. These results identify 14-3-3 λ and κ as important regulators of salt tolerance. The inhibition of SOS2 mediated by the binding of 14-3-3 proteins represents a novel mechanism that confers basal repression of the SOS pathway in the absence of salt stress.